2003
DOI: 10.1007/s10072-003-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

The transition from relapsing-remitting MS to irreversible disability: clinical evaluation

Abstract: The development of a progressive course is by far the most deleterious event in the case of a multiple sclerosis (MS) patient. It occurs in about 90% of relapsing remitting patients by 20-25 years from onset. The clinical transition to secondary progressive MS is phenotypically distinctive and both patients and physicians acknowledge that a fundamental shift in the degree of responsiveness to anti-inflammatory therapies has occurred. This review discusses the clinical studies that provided important findings r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In comparison to other trajectories, SPMS patients caused the highest costs for ancillary therapy, special equipment, hospital inpatient stays, and patient copayments. Considering indirect costs and the high risk of developing a secondary progressive course of the disease [3], the need to improve treatment options for those patients becomes obvious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to other trajectories, SPMS patients caused the highest costs for ancillary therapy, special equipment, hospital inpatient stays, and patient copayments. Considering indirect costs and the high risk of developing a secondary progressive course of the disease [3], the need to improve treatment options for those patients becomes obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Years after onset, some RRMS patients develop a secondary-progressive course (SPMS), defined by slow neurological deterioration without causal relationship to relapses [3]. A minority of patients (15%) has primary progressive MS (PPMS), characterized by a progressive and usually nonrelapsing course [4].…”
Section: Introductionmentioning
confidence: 99%
“…When carrying out an assessment, it is important to include immobility as a risk factor and it is suggested that a sustained EDSS of ≥6 (see Table 1) [79] should trigger BMD measurement by DXA. An EDSS of 6 is an appropriate cutoff as it is an established landmark in irreversible disability progression [80][81][82], fracture risk continues to rise with higher levels [39] and the use of a cane is itself a recognised risk factor for falls in MS [44,45]. The presence of a prior fragility fracture is a particularly important risk factor and may prompt treatment initiation without BMD measurement if the latter is not readily available.…”
Section: Assessment Of Bone Healthmentioning
confidence: 99%
“…3 As these cycles continue, patients accumulate disability from incomplete remissions, leading 50% into the secondary-progressive (SP) phase of the disease within 15 years. 3, 4 This phase is characterized by increasing permanent disability, fewer relapses, less inflammation and more pronounced neurodegeneration entailing chronic increase in motor, sensory and cognitive deficits and 5–10 year reduction in life expectancy. 5 …”
Section: Introductionmentioning
confidence: 99%